Longer duration of exclusive breastfeeding reduces maternal weight retention: results from the CLaB study - Michelly da Silva Alves; Maiara Aparecida Mialich Almeida; Caroline de Barros Gomes; Anna Paula Ferrari; Cristina Maria Garcia de Lima Parada; Maria Antonieta de Barros Leite Carvalhaes (Instituto Materno Infantil de Pernambuco, 2020)
Abstract Objectives: to evaluate the relation between breastfeeding and postpartum weight reten-tion. Methods: this prospective cohort study involved 641 newborns and their mothers, followed up to twelve months postpartum. Data were collected from June 2015 to February 2017. In the first interview, we investigated data regarding socioeconomic and demographic characteristics, obstetric history, weight, and gestational age of the infant at birth. Maternal weight and breastfeeding status were obtained at 3, 6, 9 and 12 months postpartum at the mother's home. A descriptive analysis of maternal weight retention according to the lactation status was performed. Multiple linear regression models evaluated the effect on exclusive breastfeeding and total breastfeeding duration on maternal weight retention at 6 and 12 months postpartum, considering potential confounders. Results: 512 and 490 mothers were evaluated at six months and at twelve months post-partum, and the mean weight retention was 1.79 (SD=5.52) and 1.69 (SD=6.69) kg, respectively. Regardless of the confounders, the mean postpartum weight reduction for each day of exclusive breastfeeding was 11 (CI95%= -0.019 to -0.003) and 16 grams (CI95%= -0.026 to -0.007) for 6 and 12 months, respectively. The total maternal breastfeeding duration had the same effect. Conclusions: longer periods of exclusive breastfeeding and total breastfeeding are associated with lower postpartum weight retention.